Ditadura e desterro: trajetórias de exilados brasileiros do golpe de 1964 nos Estados Unidos (1964-1979) - SILVEIRA, Lorenna Burjack da (2011)
This thesis aims at analyzing the trajectory of Brazilian exile victims of the 1964 military coup that opted for the United States as a place of exile in that country or were there denouncing the repressive character of the Brazilian military dictatorship. In order to more appropriately approach and understand that issue, the study presents a reflection on the characteristics of the exile as a major concern, before addressing what happened to Brazilian exile victims. Thus, this is a multidisciplinary study, developed to understand how people who have been exiled can be framed in International Law, the difficulties imposed to individuals and yet the possibilities that arise from this situation for those who experience it. Eventually, the pathological aspects of exile and torture are also discussed. The main places where Brazilian exiles were found are traced in this research, among them the United States are highlighted. This country was also responsible for granting weapons as well as logistical and financial support to the military government that overthrew late president Goulart. The relations between Brazil and the United States in the 1960s and 1970s were prioritized in this study, in an attempt to signal how the American society during this period questioned the foreign policy adopted by their country, especially with regard to Latin America. Finally, this study examines closely the link between Brazilian exiles and American intellectuals, activists and religious leaders whose purpose was to publish in the American press reports about repression and torture practiced by Brazilian military.